161 REVERSIBLE HYPONATREMIA RELATED TO PERICARDIAL TAMPONADE. Issue 1 (1st January 2007) - Shafique, R.; Sarwar, S.; Wall, B. M.; Cooke, C. R.
Abstract : Introduction: We describe a previously healthy patient who developed idiopathic pericarditis leading to symptomatic pericardial tamponade, further complicated by development of profound hyponatremia that rapidly corrected after pericardiocentesis. Case Presentation: A 59-year-old male presented with cough and fever of 2 weeks duration associated with fatigue, dyspnea on mild exertion, and ankle swelling. In addition, he reported drinking 1 to 2 gallons of water per day. On physical examination, blood pressure was 100/70 mm Hg with pulsus paradoxus of 15 mm Hg. Marked JVD and 1+ bilateral lower extremity edema were present. Serum [Na + ] was 104 mEq/L, serum osmolality 227 mosm/kg H2 O, urine osmolality 641 mosm/kg H2 O, and serum creatinine 0.7 mg/dL. Pericardiocentesis was performed with removal of 1, 700 cc of blood tinged pericardial fluid, resulting in improvement of hemodynamics, abrupt increase in urinary output, and increase in serum [Na + ] to 131 mEq/L within 24 hours. Subsequently, the patient's body weight decreased with complete resolution of peripheral edema and hyponatremia. Pericardial fluid studies showed no evidence of infectious, neoplastic, or rheumatologic etiologies. Discussion: Hyponatremia was attributed to impairment of urine diluting ability due to vasopressin-related and vasopressin-independent mechanisms in the presence of habitually high fluid intake. Low serum sodium concentration was not a manifestation of sodium depletion as shown by the presence of peripheral edema, which we have attributed to impairment of cardiac output due to progressive accumulation of pericardial effusion. Arterial underfilling in patients with reduced cardiac output is known to be associated with suppression of vagal inhibition of vasopressin release by carotid and aortic arch baroreceptors. Vasopressin-independent mechanisms designed to sustain glomerular filtration in the presence of reductions in renal blood flow may also have contributed to the development of hyponatremia. Removal of pericardial fluid by pericardiocentesis resulted in rapid improvement in systemic hemodynamics, thereby abolishing the nonosmotic stimulus for continued uninhibited vasopressin release and alterations in renal blood flow that were associated with vasopressin-independent mechanisms. In response to these changes, urine output increased promptly with excretion of large volumes of dilute urine and rapid correction of hyponatremia.